Antibody-Dependent Natural Killer Cell Activation After Ebola Vaccination. (10th December 2019) - Wagstaffe, Helen R; Clutterbuck, Elizabeth A; Bockstal, Viki; Stoop, Jeroen N; Luhn, Kerstin; Douoguih, Macaya; Shukarev, Georgi; Snape, Matthew D; Pollard, Andrew J; Riley, Eleanor M; Goodier, Martin R
Abstract: Background: Antibody Fc-mediated functions, such as antibody-dependent cellular cytotoxicity, contribute to vaccine-induced protection against viral infections. Fc-mediated function of anti-Ebola glycoprotein (GP) antibodies suggest that Fc-dependent activation of effector cells, including natural killer (NK) cells, could play a role in vaccination against Ebola virus disease. Methods: We analyzed the effect on primary human NK cell activation of anti-Ebola GP antibody in the serum of United Kingdom–based volunteers vaccinated with the novel 2-dose heterologous adenovirus type 26.ZEBOV, modified vaccinia Ankara–BN-Filo vaccine regimen. Results: We demonstrate primary human NK cell CD107a and interferon γ expression, combined with down-regulation of CD16, in response to recombinant Ebola virus GP and post-vaccine dose 1 and dose 2 serum samples. These responses varied significantly with vaccine regimen, and NK cell activation was found to correlate with anti-GP antibody concentration. We also reveal an impact of NK cell differentiation phenotype on antibody-dependent NK cell activation, with highly differentiated CD56 dim CD57 + NK cells being the most responsive. Conclusions: These findings highlight the dual importance of vaccine-induced antibody concentration and NK cell differentiation status in promoting Fc-mediated activation of NK cells after vaccination, raising a potential role for antibody-mediated NK cell activation in vaccine-induced immune responses. Abstract : We found natural killer cell degranulation and interferon γ secretion in response to recombinant Ebola virus glycoprotein and postvaccination serum samples from healthy volunteers vaccinated with the novel 2-dose heterologous adenovirus type 26.ZEBOV, modified vaccinia Ankara–BN-Filo Ebola vaccine.